2018
DOI: 10.1152/ajpheart.00301.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil improves vascular endothelial function in patients with cystic fibrosis

Abstract: These data suggest that four weeks of sildenafil treatment can improve vascular endothelial function in patients with CF, likely through an increase in NOS3 phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…In vitro treatment of human umbilical vein endothelial cells (HUVEC) with CFTR inhibitor suppressed insulin-induced NO generation, by inhibiting eNOS and AKT activation/phosphorylation [ 37 ]. Besides, ECs exposed to plasma from patients with CF treated with sildenafil demonstrated increased protein expression of phosphorylated and total eNOS compared to placebo-treated patients [ 35 ]. Overall, these findings point to decreased endothelial NO in CF ( Fig.…”
Section: Vascular Tonementioning
confidence: 81%
See 1 more Smart Citation
“…In vitro treatment of human umbilical vein endothelial cells (HUVEC) with CFTR inhibitor suppressed insulin-induced NO generation, by inhibiting eNOS and AKT activation/phosphorylation [ 37 ]. Besides, ECs exposed to plasma from patients with CF treated with sildenafil demonstrated increased protein expression of phosphorylated and total eNOS compared to placebo-treated patients [ 35 ]. Overall, these findings point to decreased endothelial NO in CF ( Fig.…”
Section: Vascular Tonementioning
confidence: 81%
“…In the same study, a positive relationship between microvascular function and lung function was found suggesting that disease severity may contribute, at least in part, to microvascular dysfunction [ 34 ]. In follow-up studies, the same group demonstrated that four weeks treatment with sildenafil (an inhibitor of phosphodiesterase 5 that enhances NO metabolism) [ 35 ] and tetrahydrobiopterin (BH 4 , a determinant of NO bioavailability) [ 36 ] increased FMD in patients with CF. In vitro treatment of human umbilical vein endothelial cells (HUVEC) with CFTR inhibitor suppressed insulin-induced NO generation, by inhibiting eNOS and AKT activation/phosphorylation [ 37 ].…”
Section: Vascular Tonementioning
confidence: 85%
“…Recently, many kinds of small molecules were synthesized to enhance angiogenesis. Sildenafil, a phosphodiesterase type 5 inhibitor, not only enhances nitric oxide metabolism but has been shown to improve vascular endothelial function [177]. Lithium was also shown to have a concentration-dependent effect on early vascular development in the chick embryo area vasculosa [178].…”
Section: Small Moleculers-based Approaches For Vascular Networkmentioning
confidence: 99%
“…In vivo endothelial cells are constantly exposed to shear stress resulting in the activation of several mechanoresponsive networks, which increase the expression of genes that regulate inflammation, such as the vascular cell adhesion molecule (Zhou et al, 2014) and bioavailability of the vasodilator nitric oxide (NO), such as endothelial NO synthase (eNOS) (Chistiakov et al, 2017). In CF, defective flowmediated dilation (FMD) of the brachial artery suggests NO bioavailability is reduced in response to shear stress (Poore et al, 2013), and improved by agents that increase NO availability (Rodriguez-Miguelez et al, 2018). This notion is further supported by the observation that acute supplementation with 20 mg/kg of oral tetrahydrobiopterin (an essential cofactor for eNOS activity) significantly improved FMD, through reduced superoxide production and increased NO, which is indicative of improved eNOS coupling in people with CF (Jeong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%